Improving epilepsy monitoring using long-term, in-home-bi-modal seizure monitoring device: clinical utilities and obstacles from a pilot study - Cho, Jaeso; Ko, Young Jun; Chung, Yoon Gi; Cho, Anna; Kim, Hunmin (Frontiers in Neurology, 2025)
ObjectiveOur study aimed to evaluate a long-term, in-home, bi-modal wearable device for seizure monitoring in epilepsy patients, assessing its applicability, clinical utility and identifying obstacles in real-life settings.MethodsA prospective pilot study involved 14 epilepsy patients at Seoul National University Bundang Hospital from May 26, 2021, to January 31, 2022. Patients used a wearable device developed for the study, featuring four-channel electroencephalogram and accelerometer sensors. Neurologists provided instructions for device usage, and bi-modal signals were recorded during daily activities. Seizures were annotated through comprehensive data review, and clinical suggestion was provided based on annotated daily seizure frequency, identification of different seizure types, and monitoring seizure patterns throughout the day.ResultsNine patients (64.3%) used the device for over 100 h, totaling 3,724 h of monitoring and capturing 1,609 seizures. The device successfully recorded various seizure types, including focal, focal with bilateral spread and generalized/bilateral onset which were further annotated by reviewers. Based on the annotated data, we were able to provide clinical suggestions based on number of seizures, identification of ambiguous seizures and monitoring of diurnal seizure pattern. Device discontinuation factors included skin irritation, patients’ unwillingness due to device appearance, and caregivers’ reluctance to use the device.ConclusionThis study demonstrates the feasibility and clinical utility of a long-term, in-home, bi-modal wearable device for seizure monitoring in epilepsy patients. The long-term data recorded by the device provided valuable clinical insights, facilitating different treatment suggestions. Addressing issues such as device comfort, appearance, and ease of use is essential for enhancing patient and caregiver adherence. The findings support the potential of wearable technology to improve epilepsy management through seizure monitoring in real-life setting.